Μετάφραση και Σχολιασμός του Κειμένου «The Significance of Intercultural Communication for Businesses and the Obstacles that Managers should Overcome in Achieving Effective Intercultural Communication» των Shum Su Kei και Rashad Yazdanifard - (:unkn) unknown (My University, 2021)
Η παρούσα πτυχιακή εργασία αφορά στην μετάφραση του άρθρου «The Significance of Intercultural Communication for Businesses and the Obstacles that Managers should Overcome in Achieving Effective Intercultural Communication». Πρόκειται, ουσιαστικά, για ένα ειδικό οικονομικό κείμενο, το οποίο πραγματεύεται τον σημαντικό ρόλο της διαπολιτισμικής επικοινωνίας στον τομέα των επιχειρήσεων, αλλά και τις δυσκολίες που πρέπει να ξεπεράσουν οι μάνατζερ των εταιρειών με σκοπό την επίτευξη αποτελεσματικής διαπολιτισμικής επικοινωνίας μεταξύ του προσωπικού. Η γλώσσα σύνταξης του πρωτοτύπου κειμένου είναι η αγγλική, ενώ η απόδοση της μετάφρασης έχει γίνει στην ελληνική γλώσσα. Σκοπό της παρούσας εργασίας αποτελεί η επίτευξη της ισοδυναμίας, αλλά και η ορθή απόδοση των οικονομικών όρων της γλώσσας-πηγή στην γλώσσα-στόχος, καθώς υπάρχει ταύτιση σκοπού, λειτουργίας και αποτελέσματος του κειμένου στις δυο γλώσσες. Τέλος, ακολουθεί σχολιασμός των μεταφραστικών προβλημάτων που έχρηζαν αντιμετώπισης προκειμένου να επιτευχθεί ο αρχικός σκοπός της μεταφραστικής εργασίας, καθώς και γλωσσάρι με την ορολογία των κειμένων.

This undergraduate dissertation concerns the translation of the article "The Significance of Intercultural Communication for Businesses and the Obstacles that Managers should Overcome in Achieving Effective Intercultural Communication". This economic text discusses the importance of intercultural business communication and the difficulties that managers should overcome in order to achieve effective intercultural communication between employees. The source text is written in English, while the target text is addressed to Greek speakers. The purpose of this paper is not only to achieve equivalence between English and Greek, but also to achieve the proper translation of the economic terms. Finally, there is a commentary on the translation problems that needed to be addressed in order to achieve equivalence, as well as a glossary of economic terminology found in the texts.
Translation and Commentary on the article "The Significance of Intercultural Communication for Businesses and the Obstacles that Managers should Overcome in Achieving Effective Intercultural Communication" written by Shum Su Kei & Rashad Yazdanifard
Keywords: διαπολιτισμική επικοινωνία, κουλτούρα, επικοινωνία, επιχείρηση; intercultural communication, culture, communication, business